Sikap Yesus kepada Sang Liyan dalam Kisah Pengusiran Setan dari Orang Gerasa dalam Markus 5:1-20 - Yohanes Krismantyo Susanta (MAGENANG : Jurnal Teologi dan Pendidikan Kristen, 2021)
By using a qualitative approach and historical critical interpretation method, this paper shows the story of Mark 5: 1-20 which tells about the exorcism of Satan from the body of the Gerasenes by Jesus. Jesus' actions are evidence of His power over the power of the evil Spirit. Not only that, Jesus' actions are a form of concern for foreigners, non-Jews. Jesus showed an example of hospitality towards strangers, namely those who were neglected and underestimated in society.